Implementation of Differentiated Discovery Models to Improve Students’ Understanding of Physics Concepts and Science Process Skills - M. Adam Buchori Muslim; Sri Hartini; Fatrahul Ani (Universitas Lambung Mangkurat, 2023)
This study aimed to improve students’ understanding of physics concepts and science process skills by combining the discovery model with the differentiated instructions approach. This study used the Collaborative Classroom Action Research method, which was carried out in two learning cycles with 36 research subjects in class X.1 at a high school in Banjarmasin. Each learning cycle comprised several meetings involving the stages of plan, do/action, see/observation, and reflection. The results from cycle I indicated that 8.33% of students had completed all the indicators of learning objectives (ILO) related to understanding the physics concept of alternative energy. Furthermore, there was an enhancement in students’ process skills, with an average increase of 37% falling into the “Less” category. The results in cycle I showed that learning activities required improvement for cycle II. The results in cycle II showed that 78% of students had completed all the ILO of understanding physics concepts, and there was an increase in students’ processing skills with an average score of 66.67% in the “Good” category. An increased understanding of physics concepts with an N-Gain value in the “High” category had a strong positive relationship with an increase in science process skills in the “Medium” category. Based on the findings of this study, it was identified that the differentiated discovery model could improve students’ understanding of physics concepts and science process skills because it could facilitate students’ learning needs, thus providing implications for students’ activeness and receptiveness to information learning physics in class.